Balance cathode-active and anode-active groups in one conjugated polymer towards high-performance all-organic lithium-ion batteries. (August 2021) - Zhao, Yang; Wu, Manman; Chen, Hongbin; Zhu, Jie; Liu, Jie; Ye, Zhantong; Zhang, Yan; Zhang, Hongtao; Ma, Yanfeng; Li, Chenxi; Chen, Yongsheng
Abstract: Organic electrode materials are promising for future rechargeable batteries owing to their potential high capacity, tunable structure, flexibility and sustainability. Thus, developing high-performance all-organic batteries is highly demanded. But so far it is still a great challenge to achieve simultaneously such desired capacities and cycling stability, particularly for the case of all-organic symmetric batteries. Here, we design and report a polymer, named Poly-BQ1, which can be used as both cathode and anode materials for high-performance all-organic symmetric Lithium-ion battery. Such a two-fold electrode material was designed and optimized by balancing/maximizing abundant cathode-active groups (C˭O, C˭N) and anode-active groups (C˭C) in one stable conjugated polymer for both the purposes of achieving high capacity and cycling stability. Thus, owing to optimized integration of redox-active C˭O, C˭N and C˭C groups in a stable conjugated backbone and minimized redox-inactive units, the all-organic battery using this single material exhibits the highest capacity (351.5 mA h g −1 at 50 mA g −1 ) among all previously reported all-organic batteries with also remarkable cycling stability (99.96% retention per cycle up to 400 cycles) and rate performance (203.4 mA h g −1 at 1 A g −1 ). Graphical Abstract: ga1 Highlights: A strategy for the design of all-organic batteries materials with simultaneously high capacity and stability is proposed. Poly-BQ1 contains maximum redox-active groups (C=O, C=N and C=C), minimum redox-inactive units and stable backbone. The all-organic symmetric battery is fabricated by using Poly-BQ1 as both cathode and anode materials. The all-organic symmetric battery shows the highest capacity (351.5 mA h g -1 at 50 mA g -1 ), good cycle and rate performance.